2008
DOI: 10.1080/10837450801949350
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Optimizing In Vitro Transdermal Permeation of Ondansetron Hydrochloride Using Nerodilol, Carvone, and Limonene as Penetration Enhancers

Abstract: The present investigation was carried out to formulate a terpene-based hydroxypropyl cellulose (HPC) gel drug reservoir system for its optimal transdermal permeation of ondansetron hydrochloride. The HPC gel formulations containing ondansetron hydrochloride (3% w/w) and selected concentrations of either nerodilol (0% w/w, 1% w/w, 2% w/w, 3% w/w, and 4% w/w), carvone (0% w/w, 2% w/w, 4% w/w, 8% w/w, and 10% w/w), or limonene (0% w/w, 2% w/w, 3% w/w, and 4% w/w) were prepared and subjected to in vitro permeation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A similar, negative effect of enhancer concentration on permeation profile of valsartan was also reported previously by Rizwan et al (26). Krishnaiah et al also studied the transdermal permeation of ondansetron in the presence and absence of different terpenes (13). They also indicated that there was no significant difference on the penetration enhancing effect of limonene depending on increasing its concentration, due to plateau effect on the drug permeation across skin above 3%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar, negative effect of enhancer concentration on permeation profile of valsartan was also reported previously by Rizwan et al (26). Krishnaiah et al also studied the transdermal permeation of ondansetron in the presence and absence of different terpenes (13). They also indicated that there was no significant difference on the penetration enhancing effect of limonene depending on increasing its concentration, due to plateau effect on the drug permeation across skin above 3%.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of permeation enhancing activity of terpenes have been attributed to increment of the drug partition into the stratum corneum and creating perturbation on the intercellular packing of the stratum corneum lipids (10,11). Limonene is a lipophilic hydrocarbon terpene (logP: 4.58), obtained from the lemon peel of Citrus lemon (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown evidence that carvone and limonene act as transdermal permeation enhancers [29]. Limonene has been found to promote skin repair and inhibit skin tumorigenesis [30,28].…”
Section: Bioactivity Profile Of Seo In the Human Dermal Fibroblast Symentioning
confidence: 99%
“…Terpenes are derived from plant essential oils, have been shown to increase the percutaneous absorption of both hydrophilic and lipophilic drugs [12,15,18,19]. It was reported that terpenes enhance the permeation of drug across the skin mainly by disrupting the highly ordered intercellular chain packing of stratum corneum lipids and thereby increasing drug diffusivity [20,21].…”
Section: Figurementioning
confidence: 99%
“…However, transdermal transport of drugs is limited due to low permeability of the uppermost layer of the skin, stratum corneum. In order to overcome that barrier and to enhance the permeability of the drugs across the skin, permeation enhancers and co-solvents, which reversibly perturb the permeability of stratum corneum or increase partition of drug to stratum corneum are included in the transdermal formulation [12][13][14].…”
Section: Figurementioning
confidence: 99%